Mathematical Modeling and Computational Tools for Efficient Water Resource Management: Optimizing Allocation and Sustainability - Suganthi, J.; Sivaraman, R.; Kumar Tambrey, Santosh; JaiSai, Tenepalli; Ahmed, K.Abrar; Das, Abhijeet (Journal of Neonatal Surgery, 2025)
Worldwide, this is an important issue of managing water resources with the need for effective distribution and sustainable use. The processes of mathematical modeling and computational techniques of water distribution which include Genetic Algorithms (GA), Linear Programming (LP), Artificial Neural Networks (ANN) and Fuzzy Logic, are considered. To conduct research with actual water demand data, the models are assessed to find out how well they achieve resource distribution, demand forecasting, and uncertainty control. Experimental results indicate that GA-driven optimization succeeds in reducing the total cost of distribution expenses by 18.3% and it improves the water allocation efficiency by 27.5% comparing to LP. Conventional regression models achieve a 84.7% accuracy in predicting demand, which is surpassed by ANN. Additionally, Fuzzy Logic effectively copes with uncertainty, to the detriment of the errors of allocation of 21.2% less compared to traditional heuristics. Examples showing comparison between the conventional resource management strategies and hybrid AI-driven approaches are provided for illustrating their advantages. Turning to AI, optimization algorithms, and decision making under the guidance of GIS leads to great improvements in water conservation, sustainability, and distributing it in a fair manner. Real-time applications, IoT based tracking and intelligence around climate should be looked into in future research. Based on a data base, the research presents an approach to water resource management that would provide sustainable and economical services of water distribution over various environmental settings.